Rethinking collaborative practices in urban processes in Algeria - Hadj Smaha, Lyazid (Bulletin of Geography. Socio-economic Series, 2025)
This article presents new strategies to address disparities in urban planning in Algeria, aiming to advance towards a more sustainable urbanism characterised by cooperative, consultative and transparent practices. It highlights the crucial role of information and communication technologies (ICT) in transitioning from a deeply rooted technocratic culture since independence to a more comprehensive and interdisciplinary culture. This research explores the imperative for a change in practices and the importance of experimentation. It underscores the impact of urban information culture on citizen participation in urban initiatives. The article also addresses the concept of cyber-democracy and the role of ICT in enhancing civic engagement in the urban decision-making process. Through a qualitative approach, the focus is on developing information-culture skills among citizens and introducing cyber-democracy as a catalyst for transformative governance.